94 An Observational Cohort Study to Evaluate Volume and Severity of Emergency General Surgery Admissions During The COVID-19 Pandemic: Is There A "Lockdown" Effect?. (4th May 2021) - McLean, R; Young, J; Musbahi, A; Lee, J X; Hidayat, H; Abdalla, N; Chowdhury, S; Baker, E; Etherson, K
Abstract: Introduction: The COVID-19 pandemic has led to changes in NHS surgical service provision. This, combined with the government-imposed lockdown, may have impacted on patient attendance, severity of surgical disease, and outcomes. This study aimed to investigate a possible 'lockdown' effect on the volume and severity of surgical admissions and outcomes. Method: Two cohorts of adult emergency general surgery admissions 30 days immediately before (16/2/2020 to 15/3/2020), and after UK government advice (16/3/2020 to 15/4/2020). Data were collected relating to patient characteristics, disease severity, clinical outcomes, and compared between these groups. Results: Following lockdown, a significant reduction in median daily admissions from 7 to 3 (p < 0.001) was observed. Post-lockdown patients were significantly older, frailer with higher inflammatory indices and rates of AKI, and more likely to present with gastrointestinal cancer, obstruction, and perforation. Patients had significantly higher rates of Clavien-Dindo Grade ≥3 complications (p = 0.001), all-cause 30-day mortality (8.5% vs. 2.9%, p = 0.028), but no significant difference was observed in operative 30-day mortality. Conclusions: There appears to be a "lockdown" effect on general surgical admissions with fewer admissions, more acutely unwell patients, and an increase in all-cause 30-day mortality. Patients should be advised to present promptly, and this should be reinforced for future lockdowns during the pandemic.